How Have COVID-19 Isolation Policies Affected Young People’s Mental Health? – Evidence From Chinese College Students - Chen, Bo; Sun, Jinlu; Feng, Yi (Frontiers in Psychology, 2020)
The breakout of COVID-19 has brought about huge influence on people’s physic and mental health. This paper aims to investigate the mental health status of young people living in isolation due to the policy response to Coronavirus disease. 992 Chinese college students (Mage = 19.45, SD = 1.41) were recruited to finish an online survey in the period of self-isolation. Seven dimensions of psychological well-being were measured, including mental status, knowledge of stress management, behavioral patterns, locus of control, academic stress, family relationships, and peer relationships. Results of cluster analysis indicated that young individuals’ mental status can be divided into three groups: high-risk (n = 61, Mage = 19.26, SD = 1.32), medium-risk (n = 627, Mage = 19.43, SD = 1.38), and low-risk (n = 304, Mage = 19.54, SD = 1.49). Moreover, results of multiple regression showed that the isolation policy has had a complex influence on the symptoms of obsessive-compulsive disorder (F (12, 979) = 44.894, p < .001), fear (F (12, 979) = 30.776 , p < .001), hypochondria (F (12, 979) = 22.530, p < .001), depression (F (12, 979) = 39.022 , p < .001), and neurasthenia (F (12, 979) = 45.735 , p < .001) via various factors. This paper also proposes a six-step intervention strategy to alleviate young people’s psychological problems while in isolation. It provides practical insights into the psychological interventions in face of the global threat.